(untitled) (VITAE Academia Biomédica Digital, 2016)
The intestinal absorption of plant secondary metabolites is required in order to exert effects on intermediary metabolism. Male rats received an aqueous extract of Bauhinia megalandra leaves (experimental) instead of drinking water (control). Their urine was subjected to differential solubility and column chromatography on silica gel; from this, a compound was partially purified, its substitution pattern, established by NMR of 1H and 13C, corresponds to benzene ortho-substituted. The compound was not present in the plant extract nor in the urine of the controls; in consequence do we suggest that it is the product of the metabolism of a secondary metabolite present in B. megalandra leaves. The rats that received the plant extract showed a discrete reduction in glycaemia of 9 %, statistically significant, and a 3.6-fold increase in the amount of glucose eliminated in the urine, which was interpreted as a renal glycosuria. The implications of these results are discussed.